A Story of Discovery and Change: What We Learned from Studying Nystagmus in Infancy and Childhood. Issue 3 (3rd July 2022) - Hertle, Richard W.
ABSTRACT: The last 40 years of clinical experience and investigation of nystagmus in infancy and childhood have resulted in a clearer understanding and characterization of the disorder and provided guidelines for the beneficial effects of increased medical, optical, and surgical treatments. Our modern understanding is due to the results of contribution by scientists and clinicians representing vision, neurology, bioengineering, genetics, and pediatrics. From this group, a new classification system was developed. The routine use of eye-movement recordings (EMR) and its characteristics have made the largest contribution to this increased knowledge. The value of EMR is due to the observation of specific waveforms, which are the basis for classification, neuro-pathophysiology, effect on vision, and a measure of nystagmus response to treatment. Successful treatment of the visual system is now directed toward associated afferent system abnormalities (decreased acuity, amblyopia, ametropia, retinal and optic pathway disease, and photophobia), centrally at the neuronal level responsible for the oscillations (oral and topical medications) and peripherally to reduce the underlying oscillation (eye-muscle surgery and botulinum toxin). Evidence over the last 40 years has shown that these treatments result in increased spatial acuity, contrast sensitivity, visual recognition time, motion processing, gaze-dependent visual acuity, and anomalous head posturing. The hope of this review is that clinicians now provide hope for these patients and families and can be counseled that nystagmus treatment is available.